2016
DOI: 10.1163/18739865-00902005
|View full text |Cite
|
Sign up to set email alerts
|

Online Presentation of Gendered Selves among Young Women in Egypt

Abstract: Social media and Facebook in particular have become an important arena of social interaction and premarital romance in Egypt. In a society where dating can potentially harm the reputation of young women, a decent public image is considered valuable symbolic capital. This is especially true for brides-to-be. Many university-educated young women have found Facebook useful for impression management. It is necessary for them to mask aspects of their behavior that may be condemned as morally inappropriate and they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…They explain how their Sahrawi Facebook friends often question pictures of them living their everyday lives in Spain without their traditional dress, the milḥafah , or participating in party-like leisure activities. Other studies with young women from North African countries (Jyrkiäinen, 2016; Menin, 2014) have noted these kinds of control practices over the lives and bodies of women. However, the distinctive patriarchal control of Sahrawi women results from the intensifying effect of the exile (Wilson, 2016) and the conflict zone scenario, which reinforce control over women and their bodies as the symbolic place to inscribe their particular moral order (Benhabib, 2006).…”
Section: Sahrawi Women In Spain and Digital Transnational Gossipmentioning
confidence: 92%
“…They explain how their Sahrawi Facebook friends often question pictures of them living their everyday lives in Spain without their traditional dress, the milḥafah , or participating in party-like leisure activities. Other studies with young women from North African countries (Jyrkiäinen, 2016; Menin, 2014) have noted these kinds of control practices over the lives and bodies of women. However, the distinctive patriarchal control of Sahrawi women results from the intensifying effect of the exile (Wilson, 2016) and the conflict zone scenario, which reinforce control over women and their bodies as the symbolic place to inscribe their particular moral order (Benhabib, 2006).…”
Section: Sahrawi Women In Spain and Digital Transnational Gossipmentioning
confidence: 92%
“…Taking and posting "selfies," or pictures taken by and of oneself, has exploded in recent years as a social media practice, due in part to the proliferation of smartphones with cameras (Taylor, 2014). Research has found that females in particular are more likely than males to post selfies that demonstrate positive physical appearance (Jyrkiäinen, 2016;Pounders et al, 2016). While posting a picture of one's face online, and (c) visibility, or the appearance of messages easily in search results or newsfeeds.…”
Section: Self-presentation In Social Mediamentioning
confidence: 99%
“…Nowadays young men and women can seek partners online and enjoy cyberspace romances (see Costa, 2016;Golzard & Miguel, 2016), Nevola, 2016). Females must make themselves available, appealing and seductive while maintaining the expected modesty and reputations of sexual purity (Jykiainen, 2016). All this is for fun, to experiment with presentations of the self.…”
Section: Family and Housing Transitions In Menamentioning
confidence: 99%